New Phenylaminopyrimidine (PAP) Anticancer Lead Compound with High Efficacy: Design, Synthesis, and in vitro Screening - El-Deeb, Ibrahim Mustafa; Han, Dong Keun; Kim, In Tae; Lee, So Ha (WILEY-V C H VERLAG GMBH, 2010)
Phenylaminopyrimidines represent a large group of new selective anticancer agents, the majority of which exert their action through the inhibition of specific kinases. In this study, a new series of N-substituted-2-aminopyrimidines has been designed and synthesized. A selected group of the synthesized derivatives was screened at a single dose concentration of 10 mu M over a panel of 60 cancer cell-lines. Compound 12e has showed great inhibitory and strong lethal effect over almost all of the 60 cell-lines and accordingly was further tested in a 5-dose testing mode to determine its IC50 values, where it showed great efficacies with intermediate potencies over the tested cell-lines. The compound was also tested over a panel of 52 kinases to explore its kinase inhibitory profile, and was found to be a selective but moderate inhibitor over FLT3 kinase.
Keywords: ACUTE MYELOID-LEUKEMIA; TYROSINE KINASE INHIBITOR; FLT3; RECEPTOR; POTENT; DRUG